2005
DOI: 10.1007/s10393-005-3869-5
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Glutathione and Carotenoid Coloration as Potential Biomarkers of Environmental Stress in Great Tits

Abstract: Measures of oxidative stress in animals may be useful biomarkers of environmental stressors, such as anthropogenic pollution. In birds, studies of oxidative stress have focused on dietary antioxidants, primarily carotenoids, which are interesting due to their multiple physiological and pigmentary functions but therefore also unspecifically related to oxidative stress. A useful complementary biomarker may be the glutathione system, commonly used in human medicine, but rarely applied to wild, terrestrial vertebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
119
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 123 publications
(139 citation statements)
references
References 38 publications
(39 reference statements)
17
119
1
Order By: Relevance
“…It has been proposed that birds like American goldfinches trade-off the use of carotenoid pigments for enhancement of the immune system versus for color display (Lozano, 1994;Moller et al, 1999;von Schantz et al, 1999). To date, all attempts to link feather coloration with oxidative stress have failed (Fitze et al, 2007;Isaksson et al, 2005;Navara and Hill, 2003). By contrast, several studies have shown that activating the immune system or inducing oxidative stress depresses bill coloration (Bertrand et al, 2006;Blount et al, 2003;Faivre et al, 2003;McGraw and Ardia, 2003;Perez et al, 2008).…”
Section: Continuousmentioning
confidence: 99%
“…It has been proposed that birds like American goldfinches trade-off the use of carotenoid pigments for enhancement of the immune system versus for color display (Lozano, 1994;Moller et al, 1999;von Schantz et al, 1999). To date, all attempts to link feather coloration with oxidative stress have failed (Fitze et al, 2007;Isaksson et al, 2005;Navara and Hill, 2003). By contrast, several studies have shown that activating the immune system or inducing oxidative stress depresses bill coloration (Bertrand et al, 2006;Blount et al, 2003;Faivre et al, 2003;McGraw and Ardia, 2003;Perez et al, 2008).…”
Section: Continuousmentioning
confidence: 99%
“…This has repeatedly been shown to result in changes in traits with potential fitness links, e.g., behavior, morphology, and reproductive investment (Gorissen et al, 2005;Isaksson et al, 2005;Fuller et al, 2007;Kempenaers et al, 2010). Likewise, several molecular and physiological parameters are also affected by the urban environment, including altered gene expression, endocrine changes, increased oxidative stress, and accelerated telomere attrition (Partecke et al, 2006;Isaksson, 2010;Atwell et al, 2012;Dominoni et al, 2013;Salmón et al, 2016;Watson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, coloration may be a reliable signal of physiological or immune condition. However, although many studies document the positive relationship between coloration and body condition or immune system, not all confirm these findings (Hõrak et al, 2004;Isaksson et al, 2005;Geens et al, 2009). Mechanisms underlying seasonal variation in coloration are not yet well understood, but some hypotheses have been advanced, such as UV bleaching, and bacterial or mechanical degradation (Delhey et al, 2010).…”
Section: Introductionmentioning
confidence: 99%